ANALYZING THE LEVEL OF THE STUDENTS’ READING COMPREHENSION IN COMPREHENDING THE NARRATIVE TEXT - Mutakhirani Mustafa; Nurfadillah Bakri (Universitas Muhammadiyah Kalimantan Timur, 2020)
The research aimed at finding out the analyzing of students’ reading comprehension at the second year of SMU Negeri 4 Bulukumba Kab. Bulukumba. The findings of this research that the researcher known the ability of the students’ reading comprehension on level at the second year of SMA Negeri 4 Bulukumba to have “Low” level. Based on the finding indicated that the second year of students’ SMA Negeri 4 Bulukumba in answer or identifying reading comprehension test, there were 60% students got correct answer in ( answer with literal) and 40% students had incorrect answer. Then 40% students had correct answer in (Interpretation) and 60% students had incorrect answer. Then 30% students had correct answer in (Critical) and 70% students had incorrect answer. Then 35% students had correct answer in (Creative) and 65% students had incorrect answer. Based on the finding about the students competence on reading comprehension level, some problems or difficulties were faced by the second grade students of SMA Negeri 4 Bulukumba in analyzing reading test with correct answer which were answer with literal, interpretation, critical and creative. Based on the result of questionnaire of students, the researcher finds out some solution from the problem of the students in reading. The students are suggested to practice reading anything that they like, for example reading a article, reading, essay, reading a book, reading newspaper and reading novel every day. The students practice interpreting what has been reading in improving reading comprehension. Keywords: Student, Reading Comprehension, Level, Analyzing